Comparative toxicokinetic profiles of multiple-components of Gelsemium elegans in pigs and rats after a single oral administration. (15th July 2020) - Cao, Jun-Jie; Yang, Kun; Yu, Hui; Long, Xue-Ming; Li, Yu-Juan; Sun, Zhi-Liang; Liu, Zhao-Ying
Abstract: Gelsemium elegans Benth ( G. elegans ) is highly toxic to humans and rats, but has insecticides and growth promoting effects on pigs and goats. G. elegans is widely used in livestock, but its in vivo dynamics are entirely unknown. Hence, we investigated the toxicokinetic profiles of G. elegans alkaloids after a single oral dose of G. elegans to pigs (1.0 g/kg) and rats (0.1 g/kg). The results indicated that rats were more susceptible to the toxicity of G. elegans than pigs. The toxicokinetic parameters of 22 and 6 components were obtained in pigs and rats, respectively. The components included 9 and 5 gelsedine-type alkaloids in pigs and rats, respectively. The Tmax results of the 5 gelsedine-type alkaloids indicated that these alkaloids were rapidly absorbed in pigs and rats. The T1/2 values of the 5 gelsedine-type alkaloids indicated that the elimination rates of these alkaloids in pigs were slower than those in rats. In addition, the Cmax and AUC results indicated that the degrees of absorption and exposure of most alkaloids in pigs were higher than those in rats except GS-2. However, the Cmax value of GS-2 (11-methoxy-14-hydroxygelsenicine) in rats was greater than that of pigs, and the Cmax value of 14-hydroxygelsenicine in pigs was merely greater than 3 times that of rats. The present results suggested that the cause of the toxicological differences species of G. elegans might be related to the degrees of absorption and exposure of gelsedine-type alkaloids, especially for the 14-hydroxygelsenicine and GS-2 in different animals. Graphical abstract: Image 1 Highlights: Toxicokinetic profiles of G. elegans alkaloids in pigs and rats were investigated firstly. The Cmax and AUC results of most alkaloids in pigs were higher than those in rats except GS-2. Toxicity of G.elegans is closely related to gelsedine-type alkaloids. The differences of the toxicological species might be related to their degrees of absorption and exposure.